Grapevine genome analysis demonstrates the role of gene copy number variation in the formation of monoterpenes - Bosman, Robin Nicole; Vervalle, Jessica Anne-Marie; November, Danielle Lisa; Burger, Phyllis; Lashbrooke, Justin Graham (Frontiers in Plant Science, 2023)
Volatile organic compounds such as terpenes influence the quality parameters of grapevine through their contribution to the flavour and aroma profile of berries. Biosynthesis of volatile organic compounds in grapevine is relatively complex and controlled by multiple genes, the majority of which are unknown or uncharacterised. To identify the genomic regions that associate with modulation of these compounds in grapevine berries, volatile metabolic data generated via GC-MS from a grapevine mapping population was used to identify quantitative trait loci (QTLs). Several significant QTLs were associated with terpenes, and candidate genes were proposed for sesquiterpene and monoterpene biosynthesis. For monoterpenes, loci on chromosomes 12 and 13 were shown to be associated with geraniol and cyclic monoterpene accumulation, respectively. The locus on chromosome 12 was shown to contain a geraniol synthase gene (VvGer), while the locus on chromosome 13 contained an α-terpineol synthase gene (VvTer). Molecular and genomic investigation of VvGer and VvTer revealed that these genes were found in tandemly duplicated clusters, displaying high levels of hemizygosity. Gene copy number analysis further showed that not only did VvTer and VvGer copy numbers vary within the mapping population, but also across recently sequenced Vitis cultivars. Significantly, VvTer copy number correlated with both VvTer gene expression and cyclic monoterpene accumulation in the mapping population. A hypothesis for a hyper-functional VvTer allele linked to increased gene copy number in the mapping population is presented and can potentially lead to selection of cultivars with modulated terpene profiles. The study highlights the impact of VvTPS gene duplication and copy number variation on terpene accumulation in grapevine.